2017
DOI: 10.1159/000485277
|View full text |Cite
|
Sign up to set email alerts
|

Effects and Interactions of Prenatal Ethanol Exposure, a Post-Weaning High-Fat Diet and Gender on Adult Hypercholesterolemia Occurrence in Offspring Rats

Abstract: Background/Aims: Prenatal ethanol exposure (PEE) could induce intrauterine programming of hypothalamic-pituitary-adrenal axis-associated neuroendocrine metabolism, resulting in intrauterine growth retardation and susceptibility to adult hypercholesterolemia in offspring. This study aimed to analyse the effects and interactions of PEE, a post-weaning high-fat diet (HFD) and gender on the occurrence of adult hypercholesterolemia in offspring rats. Methods: Wistar female rats were treated with ethanol (4 g/kg.d) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 46 publications
2
9
0
Order By: Relevance
“…This study also reported only a subtle, sex‐specific effect on glucose homeostasis (Table ), suggesting that dose rather than timing may be important in development of dyslipidemia in offspring. There also appeared to be a sex‐specific effect, although 2 studies reported stronger phenotypes in males (Gårdebjer et al., ; Pennington et al., ) while one study saw a more pronounced effect in females (Qi et al., ; Table ). Specific examination of the liver revealed PAE‐induced micro‐ and macrovesicular steatosis, increased TG concentration, and dysregulated cholesterol‐metabolizing genes (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…This study also reported only a subtle, sex‐specific effect on glucose homeostasis (Table ), suggesting that dose rather than timing may be important in development of dyslipidemia in offspring. There also appeared to be a sex‐specific effect, although 2 studies reported stronger phenotypes in males (Gårdebjer et al., ; Pennington et al., ) while one study saw a more pronounced effect in females (Qi et al., ; Table ). Specific examination of the liver revealed PAE‐induced micro‐ and macrovesicular steatosis, increased TG concentration, and dysregulated cholesterol‐metabolizing genes (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Epidemiological studies showed that the incidence of hypercholesterolemia is mainly associated with poor dietary habits, such as the consumption of foods containing excessive saturated fats and cholesterol, as well as a lack of exercise. The incidence of hypercholesterolemia is higher in women than in men [1]. The World Health Organization reported approximately 2.6 million deaths due to hypercholesterolemia [2].…”
Section: Introductionmentioning
confidence: 99%
“…33 High-fat diet feeding after prenatal ethanol exposure exacerbates cholesterol levels in adult female rats more than in male rats, potentially due to greater neuroendocrine metabolic programming in females. 34,35 Consumption of specific nutrients may alter cholesterol metabolism by interaction with sex steroids or greater susceptibility to neuroendocrine metabolic programming in females. 33 Our study has several limitations.…”
Section: Discussionmentioning
confidence: 99%